2019
DOI: 10.1111/resp.13682
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbations of fibrotic interstitial lung diseases

Abstract: Background and objective: Acute exacerbation (AE) is a severe complication of idiopathic pulmonary fibrosis (AE-IPF). In 2016, an international working group revised its definition and diagnostic criteria; however, few studies have assessed the frequency and prognosis of AE in patients with other fibrotic interstitial lung diseases (FILD). Methods: We used data from 1019 consecutive interstitial lung disease (ILD) patients initially evaluated between January 2008 and July 2015. All subject diagnoses were made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 40 publications
11
99
4
Order By: Relevance
“…In our study, the GAP index was a risk factor for both death and AE-ILD. At least one of these ndings has been described in earlier investigations [18,[22][23][24][25][26][27], even though this has not been veri ed in all studies [9,28]. We also demonstrated that AE-ILDs can occur at any phase of the disease in a cohort involving both IPF and non-IPF patients, a nding which is a known feature of IPF, making the disease course di cult to predict [12,29].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our study, the GAP index was a risk factor for both death and AE-ILD. At least one of these ndings has been described in earlier investigations [18,[22][23][24][25][26][27], even though this has not been veri ed in all studies [9,28]. We also demonstrated that AE-ILDs can occur at any phase of the disease in a cohort involving both IPF and non-IPF patients, a nding which is a known feature of IPF, making the disease course di cult to predict [12,29].…”
Section: Discussionmentioning
confidence: 56%
“…54%, in our study population. In the previous studies, presenting data on GAP and its effect on mortality, the prevalence of AE-ILD has varied between 20-40% [18,22,23], these discrepancies may be caused by different types of study protocols, e.g. we included only non-electively hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The studies mentioned above, however, did not use the current definition of AE-IPF in their inclusion criteria, and in addition, one study included patients treated in the ICU, 8 which is known to be a risk factor for death, at least in patients with IPF. 28 The other published studies concerning AE-FILD have been conducted in Japan, [9][10][11][12][13][14] of which only one demonstrated longer survival of patients with non-IPF compared with that of IPF 13 ; in another study, the prognosis of AE-IPF compared with other FILDs was even better. 9 Altogether, it can be stated that the earlier publications focusing on acute respiratory worsening or AE of IPF or non-IPF FILDs have consisted of small and heterogenic study populations with variable inclusion criteria, which complicate making comparisons between the investigations.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4] The phenomenon of acute exacerbation (AE) has been associated with high mortality in IPF, and AEs also seem to cause significant mortality in other FILDs. [5][6][7][8][9][10][11][12][13][14] According to previous studies, every year about 5%-15% of patients with IPF will experience an AE. 5 13 Recently, it was shown that the incidence of AE or death in a study consisting of various types of patients with FILD was 7.8% per year.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with AE of IPF were eligible for the review. Idiopathic NSIP was not included in this study because there has been no clear evidence that the prognosis of AE of idiopathic NSIP is the same as that of AE of IPF although it constitutes CFIP alongside of IPF [19]. IPF was diagnosed based on previously published joint statement of American Thoracic Society/European Respiratory Society/Japanese Respiratory Society/Latin American Thoracic Association (ATS/ERS/JRS/ALAT) or its recent update [10,20].…”
Section: Eligibility Criteria Subjectsmentioning
confidence: 99%